Relationship between the Critical Temperature of Thermal Explosion and the Thickness of a Lead Azide Plane Crystal; Combustion, Explosion, and Shock Waves; Vol. 54, iss. 1 - Khaneft A. V. Aleksandr Villivich (2018, 2018)
Title screen